MORPHOLOGICAL CHARACTERISTICS OF VIZIANAGARAM GOATS* (Indian Journal of Animal Production and Management, 2023)
In a field study covering 240 farmers spread over 80 villages in 16 mandals, data were collected on the morphological characteristics of local goats in Vizianagaram district of Andhra Pradesh. The predominant coat colour was bicolour (48.64%), followed by single colour (44.22%) and multi colour (7.14%). The bicolour pattern consisted of mainly black and white whereas, single coat colour pattern consisted of mainly black followed by white colour. The head profile of majority of local goats was straight (80.18%), followed by slightly convex (19.82%). Most of the goats (99.28%) had pendulous ears. Majority of goats (68.38%) did not have beard. Wattles were present in 50.88 per cent of goats and were present in both sexes. Both the sexes were horned (91.65%), but few were polled (8.35%).
Keywords: Goat; Vizianagaram goats; Morphological characteristics